2000
DOI: 10.1108/00251740010326333
|View full text |Cite
|
Sign up to set email alerts
|

Toward a conceptual framework of employee volunteerism: an aid for the human resource manager

Abstract: The purpose of the research is to provide HR managers with some guidance, as they develop employee volunteer programs to meet specific workforce needs. Structured interviews were conducted with eight employees. The data suggest that employees who volunteer time believe that such experiences benefit them personally and improve their ability to perform their work duties. There were slight differences in program type, with those employees involved in programs characterized by high management support and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 6 publications
2
63
0
4
Order By: Relevance
“…ESV demonstrates a real commitment to the local community and has an impact on the perceptions of customers and other stakeholders, such as employees and suppliers. Establishing contacts with non-profit organisations not only creates a positive local profile 15 but can have an affirmative effect on corporate image and reputation 16 . Through increasing profitability and brand reputation a company"s competitive edge increases 17 .…”
Section: Introductionmentioning
confidence: 99%
“…ESV demonstrates a real commitment to the local community and has an impact on the perceptions of customers and other stakeholders, such as employees and suppliers. Establishing contacts with non-profit organisations not only creates a positive local profile 15 but can have an affirmative effect on corporate image and reputation 16 . Through increasing profitability and brand reputation a company"s competitive edge increases 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, in an economic recession context, CV has tended to be seen as superfluous, dispensable, and away from the core business (Plagnol and Huppert, 2010). Leaving aside these more macroeconomic variables, literature show that time is the main barrier to employee involves in CV (Geroy, et al, 2000). Likewise, the fact that managers are not sufficiently aligned with CV project can be a brake itself (Peloza and Hassay, 2006).…”
Section: Motivations Arising From Job Satisfaction Autonomy and Selfmentioning
confidence: 99%
“…For example, literature has indicated that personal needs are related with: values (altruism), understanding (learning experiences), social experiences, carreer (skills professional), protection (ego and guilty for being luckier), enhacement, and self-esteem (Clary et all, 1998). In parallel to achieving those objectives, certain skills are usually developing (Thoits and Hewitt, 2001;Geroy, et al, 2000;Lee and Higgins, 2001), such as improving communication skills -speaking public or presentations-leadership, mentorship, projects management, ability to motivate others and provide feedback, teamwork and time management (Jones, 2016). Literature indicates many other motivations to explain that employees participate in CV.…”
Section: Brakes and Barriers Of Corporate Volunteeringmentioning
confidence: 99%
See 2 more Smart Citations